Interview-Literatur: Tom Kummers Fake-Interviews und die Folgen. Issue 1 (2nd January 2016) - Pabst, Stephan
Abstract : The fictional interviews by journalist Tom Kummer, which were published between 1996 and 2000 in various German magazines, have been read by the media exclusively as cases of an individual's moral failure. However, researchers are increasingly reading the interviews as fakes, that is, as a phenomenon on the border between forgery and fiction, lending to the conditions of credibility of journalistic writing and particularly to an interview's reflexive quality. The article engages with the media and genre-specific conditions of fake interviews, and with the concept of reality that they presuppose, as well as with the consequences they have for the self-reflexivity of journalistic interviews and their literary applications.